[OP.3C.07] BLOOD PRESSURE, HEART RATE AND DOUBLE PRODUCT IN A POOLED COHORT: THE JAPAN ARTERIOSCLEROSIS LONGITUDINAL STUDY (JALS). (September 2017) - Asayama, K.; Hozawa, A.; Taguri, M.; Ohkubo, T.; Tabara, Y.; Suzuki, K.; Ando, T.; Harada, A.; Ohashi, Y.; Ueshima, H.; Toyoshima, H.; Imai, Y.
Abstract : Objective: To figure out the characteristics of blood pressure (BP), heart rate, and double products among a population sample of the Japan Arteriosclerosis Longitudinal Study (JALS). Design and method: JALS is a collaborative project of prospective cohort studies in Japan with a common protocol. We pooled individual records from 1999–2005 for 99, 207 participants in 25 community-based cohorts and 7 work-site based cohorts. The data were analysed to provide information on BP, heart rate, and double products according to age-sex groups and use of antihypertensive medication. Results: Average BP was 130/77 mmHg among men and women combined. Among untreated individuals, systolic BP level increased with an increase in age (Figure A), whereas diastolic BP reached a ceiling around the age of 60 (Figure B). Average systolic BP of treated participants was around 140 mmHg irrespective of age (Figure A), while diastolic BP level decreased linearly with an advance in age (Figure B), and 56.4% of treated participants had a BP of 140/90 mmHg or over. Heart rate did not differ across age groups or treatment status. Double product, also called rate-pressure product calculated by multiplying systolic BP and heart rate, increased with an increase in age among untreated individuals which is mediated by an age-dependent increase in systolic BP, while it first decreased and then increased along with the advance in age among treated individual. Conclusions: The current JALS project provides descriptive information on BP, heart rate, and double product, and demonstrates inadequate BP control across age and sex in Japan where an average life expectancy is the longest in the world. Figure. No caption available.